Feeling of guilt explains why people react differently to resource depletion warnings - Thomas Baumgartner (Nature Portfolio, 2021)
Abstract Despite insistent warnings from climate scientists, the global environmental situation is further deteriorating. To date, only very few studies have investigated the impact of warnings on sustainable decision-making in controlled laboratory settings. Moreover, the few existing studies mainly looked at average warning reactions rather than taking individual differences into account. Here, we investigated individual differences in the reaction to resource depletion warnings and scrutinized the impact of emotions on behavioural changes by applying a resource dilemma task with warnings. Data-driven and model-free cluster analyses identified four different types of consumption behaviour. Importantly, guilt was positively related to sustainable decision-making after warnings. In contrast, a lack of guilt was associated with no behavioural change or even worse with more unsustainable behaviour after warnings. These findings contribute to the debate over effective climate change communication by demonstrating that issuing warnings about the climate crisis only leads to the intended behavioural changes if people experience guilt.